Malaysian pronunciation: is it wrong to sound Malaysian? / Nor Asni Syahriza Abu Hassan ... [et al.] - Abu Hassan, Nor Asni Syahriza; Wan Ismail, Wan Nurul Fatihah; Ahmad Zaidi, Nurul Nadwa; Hasman, Nurul Hijah (Universiti Teknologi MARA, Kedah, 2021)
The status of English l anguage in Mala y s ia has been long known and understood by citizens of Malaysia. From its native countries, English has spread to all parts of the world. In Malaysia, English was brought by the British colonialists. Now, English is the second official language in the country and it serves as the medium of professional communication. As English is now used globally, Malaysian English (ME) has emerged to be accepted as a legitimate variety of English. Phonology is one of the notable differences between ME and native English, mainly British English. Due to the differences, there have been endless debates and discussions whether it is wrong to sound Malaysian. The focus of this conceptual paper is to highlight the common mistakes among Malaysians, in particular the learners of the English language so improvements can be made. Also, it highlight the importance o is to f good use of English when conversing. Although pronunciation are challenges and problems in understood and acknowledged, suggestions are made so that the level of pronunciation among Malaysians can be improved.